BODY DISCIPLINE IN THE MOVIE “TURNING RED”: FOUCALDIAN DISCOURSE - Neisya, Neisya; Aprilia, Fitria; Triwulandari, Elga (Elite Laboratory Jurusan Sastra Inggris Universitas Bangka Belitung, 2024)
This research explores the concept of body discipline and its implications in the movie